Toward a taxonomy of newspaper information quality: An experimental model and test applied to Venezuela dimensions found in information quality - Romero-Rodríguez, Luis M; Aguaded, Ignacio (Journalism, 2017)
The quality of information from communication media is a topic that has been dealt with by various theorists through the analysis of the final products of information. This research work offers an analysis model of the quality of information of printed news media by the use of three indexes of categories and structured dimensions that will allow for the assessment and evaluation of the quality of information from the media, and the identification of the incidence of political-economic conditions of the journalistic environment’s macro-environment. For this, an experimental test of two Venezuelan media outlets was performed. Their use allowed us to conclude that political polarization and discourse of social confrontation, as well as economic factors such as inflation and pay scales had a proportionally direct effect on the quality of information products.
Keywords: information quality; mass media; newspaper; press; print media; JCR; Scopus